Identifying conditions for a third dose intention of COVID-19 vaccination in college students: A fuzzy-set qualitative comparative analysis - Wanqin Gao; Yulin Zhang; Gang Yin (Frontiers Media S.A., 2022)
BackgroundDuring the pandemic, a third dose of the COVID-19 vaccine effectively reduces the proportion of severe cases in those infected, but vaccine hesitancy impedes this reasonable prevention method. Epidemic control in China is being tested due to the large population base, especially in crowded places like college campuses. This study aimed to explore the configuration paths of psychological antecedents for college students to receive a third COVID-19 vaccine.MethodsAn anonymous cross-sectional survey was carried out in five universities in Wuhan using convenience sampling. A long version of the 5C 7-point Likert scale was used to measure college students' intention and psychological antecedents on the third dose of the COVID-19 vaccine. A fuzzy-set Qualitative Comparative Analysis (QCA) approach was performed to explore the configuration of conditions to the vaccination willingness.Results31.67% of respondents surveyed did not receive their third dose of the COVID-19 vaccine. The score of intention to get the vaccine for college students who did not receive the booster vaccine was 4.93 (±1.68). Average scores of 5.19 (±1.24), 4.35 (±1.75), 4.02 (±1.45), 5.84 (±1.23), and 4.61(±1.32) were reported for confidence, complacency, constraints, calculation, and collective responsibility in them. QCA showed high confidence and collective responsibility playing a central role in third dose vaccination intention. Meanwhile, low confidence and collective responsibility are the core conditions of low vaccination willingness.ConclusionEliminating vaccine hesitancy necessitates focusing on the psychological antecedents of vaccination intentions to identify critical targets for policy and interventions. This study identified trust and collective responsibility are core elements of the psychological antecedents of college students' intention to receive the booster vaccine for COVID-19. To achieve herd immunity as soon as possible, health administration and campus can start with vaccine confidence-building and collective responsibility cultivation to take appropriate actions and measures to improve coverage of the booster vaccination.